THE RHYTHM OF RITUALS OF TAMIL NADU – A DESCRIPTIVE STUDY - Udayakumar, Bhavani; S, Subbulakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
A ritual is a set of actions performed in a particular order with religious, cultural, or socially significant meaning. Religious ceremonies are usually followed as prescribed in religious scriptures as a long-standing practice. Music and dance have always had their place among humans that can be traced back to as early as the ancient civilisations of the world. Even to date, some of the most common factors that can be seen as a part of rituals, irrespective of cultural differences, might be music, dance, and food. Rhythm is ever prevailing in all nature and even in manmade things. The music and dance are mere extensions of the rhythm of an individual or a community that is expressed outward. Hence, they are inevitable in the rituals too. India, with a rich tradition of religion and arts, influences the community to a greater extent. This study uses a descriptive research methodology to analyse the Rituals of Tamil Nādu involving music and dance. The mythological background of rituals and music, rituals regarding the temple, kingdom, folk rituals, and commoners involving music or dance have been discussed. These rituals are slowly fading with the increase in the modernisation of the world. With technologies replacing several artists, it can also be considered the last resort to record and archive arts and rituals on the verge of extinction. Some ritualistic arts might not be saved even with help as they follow a rigorous customary tradition that can only be carried on by the family line. Rituals involving superficial beliefs that affect or hurt the physical aspects of humans or animals might be avoided. However, the arts related to it must be encouraged to document to be passed on to the future generation.